'More together than apart': The evaluation of a virtual course to improve mental health and well‐being of adults with intellectual disabilities during the COVID‐19 pandemic. Issue 6 (28th July 2022) - St. John, Laura; Volpe, Tiziana; Jiwa, Muhammad Irfan; Durbin, Anna; Safar, Yousef; Formuli, Fatima; Thakur, Anupam; Lake, Johanna; Lunsky, Yona
Abstract: Background: To address the growing concerns over poor mental health experienced by adults with intellectual disabilities due to the COVID‐19 pandemic, a national virtual mental health course was delivered and evaluated. Methods: This mixed methods study utilized both qualitative and quantitative assessments. Participants were 27 adults with intellectual disabilities who participated in the 6‐week course. Participants completed measures of self‐efficacy and well‐being at three time points and qualitative satisfaction measures at post and follow‐up. Results: Attendance was high and the course was feasible and acceptable to participants. Positive changes related to mental health self‐efficacy were detected ( p = .01), though mental well‐being did not improve. Conclusion: The study provided evidence for the feasibility and value of the course for this population. Future research should examine how virtual courses could support the population in terms of pandemic recovery and how courses may work for individuals who are less independent.